Applied improvisation and transdisciplinary simulation: a necessity for any health curriculum? - De Wever, Julie; Hainselin, Mathieu; Gignon, Maxime (Frontiers in Medicine, 2023)
From practising a procedure, such as a lumbar puncture to explaining the aim and method and listening to concerns, the practice of health professionals requires a range of skills, often classified into technical and non-technical skills. Gestures and procedures can be taught, and as can empathy and communication skills. This article introduces an innovative approach to unite both necessary skills.The specific framework of improvisational theatre (improv) has widespread application, including the training of health professionals (health training improv). By sharing close context and skills, health training improv provides a valuable, safe and effective learning environment, which allows practitioners to practice exercises and situations that align with objectives.We created a transdisciplinary team to develop Health Professional Training Improv (HPTI), bringing together the fields of health, psychology, simulation and arts. Since 2019, various health student groups (nurses, midwives, medical doctors, speech therapists) participated in a 16-hour applied improv training under the supervision of a professional improv facilitator. Additionally, drama students completed applied improv for health courses to act as simulated patients, with a view to transdisciplinary improv simulation sessions at SimUSanté (a multidisciplinary health simulation facility located in France).Students' feedback emphasized their interest in HPTI, the realism of the simulation session and the skills they felt had improved. This feedback needs supplementation with quantitative data from standard assessments. This rich pedagogical and research framework development, based on a transdisciplinary approach, has brought together different fields to prepare students for real patients encounters. It is essential to sustain this training and conduct research to evaluate the curricula.